Microfluidic cell surface antigen expression analysis using a single antibody type. Issue 4 (27th January 2016) - Zhang, Ye; Pappas, Dimitri
Abstract : A single-chip approach to capture and isolate cells based on differences in antigen expression. Abstract : Antigen expression plays a significant role in clinical studies, pathology, biology and chemistry. The type and degree of antigen expression can provide information for disease diagnosis/monitoring and is used for phenotype analysis of cells. In this work, an affinity capture method was developed to capture cells based on antigen expression differences in a single microfluidic chip. Microfluidic chips with two affinity regions—at different antibody concentrations—captured two cell types based on differences in the expression of a single antigen. Using herringbone-modified capture channels, a separation purity of 95% and a capture efficiency of 15% were achieved under continuous-flow conditions. We observed that the capture ratio of Ramos B lymphocytes and HuT 78 T lymphocytes matched the expression ratio of CD71 for the two cell lines ( R 2 = 0.94). To further validate our analytical method, Ramos B lymphocytes were spiked into blood samples to demonstrate performance with a complex sample. Expression ratios matched conventional flow cytometry measurements over a 40-fold difference, and the sample enrichment was 9.5×. This method has proven to be a robust system to measure the differences in antigen expression, and can be used to distinguish cells without having a unique surface antigen if the expression level is sufficiently high in one cell type.